LIBYAN-AFRICAN RELATIONS: FROM ARAB NATIONALISM TO THE AFRICAN UNION (1969–2011) – A HISTORICAL STUDY - Dr. Sabah Algam Musa (Scholars Digest Publishing, 2025)
This research aims to study the relations between Libya and Africa during the period from 1969 to 2011, focusing on the significant shift in Libyan foreign policy, which transitioned from an emphasis on Arab nationalism to a deep engagement with African affairs and the establishment of the African Union. The research indicates that this shift was not merely a tactical change, but rather an embodiment of redefining Libya's identity and its regional role during Muammar Gaddafi's era. The study reveals that the key factors driving this shift included disappointment with the continued failure of Arab unity projects, Gaddafi's desire to find a new leadership role after the decline of his influence in the Arab world, and the need to break the international isolation imposed on Libya in the 1990s. Economic interests also played an important role in this shift, as the goal was to diversify partners and secure resources. In addition, this phase witnessed an ideological shift for Gaddafi from Arab nationalism to "Africanism," which became the strategic depth of Libya. Libya relied on a set of tools to enhance its influence on the African continent, including active diplomacy (such as mediation in conflicts and active participation in the Organization of African Unity), as well as significant financial support (aid, loans, and massive investments in infrastructure projects like telecommunications and transportation), in addition to military training and support. The pinnacle of this role was Libya's leadership in the establishment of the African Union, where Gaddafi provided significant financial and political support, directing his call toward an ambitious unification vision to establish the "United States of Africa." However, the research highlights the contradictions between the proclaimed slogans (such as unity and development) and the pragmatic interests (such as leadership, influence, and intervention), which sometimes affected Libya's credibility. The central nature of Gaddafi's personality also made Libyan politics volatile and unpredictable. After 2011, the fall of Gaddafi's regime led to a significant decline in Libya's influence in Africa and resulted in negative repercussions on the region's stability, particularly in the Sahel and Sahara region, highlighting the fragility of a role that relied on a single individual. In conclusion, the research concludes that Libyan-African relations left a complex legacy, combining positive contributions to unity and development with negative impacts on regional stability.
Keywords: Libyan-African relations, Muammar Gaddafi, Arab nationalism, African Union, Organization of African Unity, Libyan foreign policy, African unity, international sanctions, African development, Libyan interventions.